Induction of the viable but non-culturable state in bacterial pathogens by household cleaners and inorganic salts - Christian Robben (Nature Portfolio, 2018)
Abstract Effective monitoring of microbial pathogens is essential for a successful preventive food safety and hygiene strategy. However, as most monitoring strategies are growth-based, these tests fail to detect pathogenic bacteria that have entered the viable but non-culturable (VBNC) state. The present study reports the induction of the VBNC state in five human pathogens by commercially available household cleaners in combination with inorganic salts. We determined that non-ionic surfactants, a common ingredient in household cleaners, can induce the VBNC state, when combined with salts. A screening study with 630 surfactant/salt combinations indicates a correlation between the hydrophobicity of the surfactant and VBNC induction in L. monocytogenes, E. coli, S. enterica serovar Typhimurium, S. aureus and toxin-producing enteropathogenic E. coli. Cells that were exposed to combinations of surfactants and salts for 5 min and up to 1 h lost their culturability on standard growth media while retaining their ATP production, fermentation of sugars and membrane integrity, which suggests intact and active metabolism. Screening also revealed major differences between Gram-negative and Gram-positive bacteria; the latter being more susceptible to VBNC induction. Combinations of such detergents and salts are found in many different environments and reflect realistic conditions in industrial and domestic surroundings. VBNC cells present in industrial environments, food-processing plants and even our daily routine represent a serious health risk due to possible resuscitation, unknown spreading, production of toxins and especially their invisibility to routine detection methods, which rely on culturability of cells and fail to detect VBNC pathogens.